Expression of tumor necrosis factor-alpha receptor 2 and interleukin-1 in middle ear cholesteatoma - Vranješ , Dalibor; Spremo, Slobodan; Gajanin, Radoslav; Špirić, Sanja; Amidžić, Ljiljana; Novaković-Bursać, Snježana (Vojnosanitetski pregled, 2021)
Background/Aim. Cholesteatoma is characterized by progressive growth with the erosion of surrounding bone due to pressure effects, enzymatic activity and activation of osteoclasts.  The aim of this study was to examine the expression levels of tumor necrosis factor (TNF)-alpha receptor 2 (TNF R2) and interleukin-1 (IL-1) in chronic otitis media (COM) with and without acquired cholesteatoma and correlate them with the degree of bone destruction. Methods. The study included 178 patients of both sexes, aged 5–75 years, who underwent microsurgical treatment for COM, with and without cholesteatoma at the Ear, Nose and Throat Department, University Clinical Center of Republika Srpska (UCC RS), Banja Luka from 2015 to 2018. Based on cholesteatoma presence, the patients with COM were divided into two groups: with cholesteatoma (CCOM) (n = 97) and without cholesteatoma (COMWC) (n = 81). Samples of cholesteatoma perimatrix in the CCOM group and tympanic cavity inflamed mucosa in the COMWC group were collected intraoperatively. Intraoperative exploration of the middle ear included the status of the ossicular chain, individual ossicles, osseous walls of the external auditory canal (EAC) and tympanic cavity. Expression levels of TNF R2 and IL-1 were investigated by immunohistochemical analysis of tissue samples obtained during ear surgery. Results. The correlation between the level of osteodestruction and the presence of cholesteatoma was significant (p
Keywords: interleukin-1; cholesteatoma; chronic disease; otitis media; bone resorption; receptor, tumor necrosis factor-alpha